Pengaruh Motivasi, Lingkungan Kerja dan Human Relation Terhadap Kinerja Pegawai Dinas Pemuda Olahraga, Pariwisata dan Ekonomi Kreatif di Provinsi Sulawesi Barat - Kiki Wirdayani Sari; Kaesnaeny Karim; Etik Prihatin (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
ABSTRACT This study aims to analyze the influence of motivation, work environment, and human relations on employee performance at the Youth, Sports, Tourism, and Creative Economy Agency of West Sulawesi Province. This study uses a quantitative approach with a survey method. The population in this study were all employees at the Youth, Sports, Tourism, and Creative Economy Agency of West Sulawesi Province, totaling 130 people. Sampling was determined using the Slovin formula with a 10% error rate, resulting in a sample size of 57 respondents. Data collection techniques were carried out through observation and distribution of questionnaires using a Likert scale. Data analysis used multiple linear regression analysis to determine the effect of each independent variable on the dependent variable. The results of the study indicate that motivation has a positive and significant effect on employee performance. The work environment does not have a positive and significant effect on employee performance. Human relations also have a positive and significant effect on employee performance. This indicates that better work motivation, a conducive work environment, and harmonious working relationships between employees will improve employee performance at the Youth, Sports, Tourism, and Creative Economy Agency of West Sulawesi Province. Keywords: Motivation, Work Environment, Human Relations, Employee Performance.